Results 2 Years After Matrix-Associated Autologous Chondrocyte Transplantation Using the Novocart 3D Scaffold: An Analysis of Clinical and Radiological Data. (July 2014) - Zak, Lukas; Albrecht, Christian; Wondrasch, Barbara; Widhalm, Harald; Vekszler, György; Trattnig, Siegfried; Marlovits, Stefan; Aldrian, Silke
Background: A range of scaffolds is available from various manufacturers for cartilage repair through matrix-associated autologous chondrocyte transplantation (MACT), with good medium- to long-term results. Purpose: To evaluate clinical and magnetic resonance imaging (MRI) outcomes 2 years after MACT on the knee joint using the Novocart 3D scaffold based on a bilayered collagen type I sponge. Study Design: Case series; Level of evidence, 4. Methods: Of 28 initial patients, 23 were clinically and radiologically evaluated 24 months after transplantation. Indications for MACT were chondral or osteochondral lesions on the knee joint with a defect size >2 cm 2, no instability, and no malalignment (axis deviation <5°). Then, MRI was performed on a 3-T scanner to assess the magnetic resonance observation of cartilage repair tissue (MOCART) and 3-dimensional (3D) MOCART scores. A variety of subjective scores (International Knee Documentation Committee [IKDC], Knee injury and Osteoarthritis Outcome Score [KOOS], Noyes sports activity rating scale, Tegner activity scale, and visual analog scale [VAS] for pain) were used for clinical evaluation. Results: Two years after MACT, the MRI evaluation showed a mean MOCART score of 73.2 ± 12.4 and a 3D MOCART score of 73.4 ± 9.7. Clinical results showed mean values of 69.8 ± 15.2 for the IKDC; 51.6 ± 21.2, 86.5 ± 13.9, 54.5 ± 23.6, 65.0 ± 8.0, and 91.5 ± 10.6 for the KOOS subscales (Quality of Life, Pain, Sports and Recreation, Symptoms, and Activities of Daily Living, respectively); 77.5 ± 12.7 for the Noyes scale; 4.4 ± 1.6 for the Tegner activity scale; and 1.8 ± 1.7 for the VAS, with statistically significant improvement in all scores other than KOOS-Symptoms. Conclusion: Undergoing MACT using the Novocart 3D scaffold is an applicable method to treat large focal chondral and osteochondral defects, with good short-term clinical and radiological results.